Case Study: Kenya’s investment in innovation for sustainable agricultural intensification - Dalberg Asia (Commission on Sustainable Agriculture Intensification, 2021)
Agriculture plays a key dual role in Kenya. It provides livelihoods for 75% of the country’s population and supports 80% of its rural population. Crucially, it helps the country to meet its food security goals, which is increasingly challenging with Kenya’s population doubling over the last 25 years. Agricultural innovation in general, and SAI innovation in particular are important for Kenya given this central role of agriculture in Kenya along with the key role Kenya plays in East Africa.